2001
DOI: 10.1002/ajh.1172
|View full text |Cite
|
Sign up to set email alerts
|

Temporal variations in plasma vitamin K and lipid concentrations and clotting factor activity in humans

Abstract: There is no information available on temporal variability in plasma vitamin K concentrations and its relationship to coagulation processes. We investigated the possible existence of temporal changes in plasma vitamin K and lipid concentrations and activity of clotting factors II, VII, IX, and X and relationships between these variables. Plasma vitamin K and lipid concentrations and clotting factor activity were measured at four-hour intervals for 28 hours in a group of healthy volunteers. Temporal variations e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
20
1
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 22 publications
(24 reference statements)
2
20
1
1
Order By: Relevance
“…Serum vitamin K transport also can significantly alert by serum lipids mostly triglycerides [11]. All of these factors can affect vitamin K-dependent coagulation factors activation and therefore reduce their activity in blood stream [9,11]. In the current patient, high serum lipids, the only factor that we found that can affect patient's coagulation factors and causes severe bleeding and hospitalization.…”
Section: Editorial Open Accessmentioning
confidence: 74%
See 3 more Smart Citations
“…Serum vitamin K transport also can significantly alert by serum lipids mostly triglycerides [11]. All of these factors can affect vitamin K-dependent coagulation factors activation and therefore reduce their activity in blood stream [9,11]. In the current patient, high serum lipids, the only factor that we found that can affect patient's coagulation factors and causes severe bleeding and hospitalization.…”
Section: Editorial Open Accessmentioning
confidence: 74%
“…Acquired deficiency can results in different conditions including liver disease and malabsorption [8,9]. In the present study, we reported a woman with acquired vitamin K-dependent coagulation factors with extensive menorrhagia.…”
mentioning
confidence: 76%
See 2 more Smart Citations
“…Early research indicated that there were temporal variations in lipid concentrations and activities of the four clotting factors which might be influenced by lipid metabolism [31,32] . In the present study, no significant was found in lipid concentrations between the diseased and control subjects, and bivariate correlation analyses showed no significant relationship between each of the four clotting factors and levels of cholesterol and triglycerides (data not shown).…”
Section: Discussionmentioning
confidence: 99%